2018
DOI: 10.1007/s00384-018-3108-5
|View full text |Cite
|
Sign up to set email alerts
|

Meta-analysis of the prognostic value of CpG island methylator phenotype in rectal cancer

Abstract: PurposeThe pathological and prognostic importance of CpG island methylator phenotype (CIMP) in rectal cancer, as a sub-population of colorectal cancer, is unknown. A meta-analysis was preformed to estimate the prognostic significance of CIMP in rectal cancer.MethodsA systematic search was performed of PubMed, Embase, MEDLINE, PubMed Central, and Cochrane electronic databases for articles pertaining to CIMP and rectal cancer. Articles were analysed and data extracted according to PRISMA standards.ResultsSix stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 37 publications
1
3
0
1
Order By: Relevance
“…With regard to the heterogeneity in the BRAF and p53 analyses, it is noteworthy that the rate of BRAF mutations was higher in the mucinous groups in all included studies, and the rate of p53 alterations was lower in the mucinous groups in all but one study. Heterogeneity may have been underestimated in the CIMP analysis, given the difficulties reported in determining and assigning CIMP status owing to the variety of markers currently used. The majority of studies included in the analysis were retrospective, which may increase the risk of sampling bias and data collection bias.…”
Section: Discussionmentioning
confidence: 99%
“…With regard to the heterogeneity in the BRAF and p53 analyses, it is noteworthy that the rate of BRAF mutations was higher in the mucinous groups in all included studies, and the rate of p53 alterations was lower in the mucinous groups in all but one study. Heterogeneity may have been underestimated in the CIMP analysis, given the difficulties reported in determining and assigning CIMP status owing to the variety of markers currently used. The majority of studies included in the analysis were retrospective, which may increase the risk of sampling bias and data collection bias.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, assessing the methylation status of specific genes could be useful in clinical practice. Indeed, it could represent a biomarker for the detection or monitoring of specific diseases such as CRC, and more particularly of the serrated lesions that are associated with a CIMP signature [58,59,60]. For instance, a recent study reported on a positive correlation between CIMP and older age in SSA/Ps, indicating a lower risk of developing a malignancy in young patients [61].…”
Section: Cpg Island Methylator Phenotype An Epigenetic Signature mentioning
confidence: 99%
“…The primary findings of Chapter 3 were that a clear association was demonstrated between the presence of pEMVI and male sex, T and N stage, AJCC classification, and the requirement for adjuvant chemotherapy 258 . This study confirms the association of EMVI with worse clinicopathological features and that these translated into a statistically significant survival disadvantage, in keeping with the findings of other authors 280 In order to gain a fuller understanding of the role of CIMP in EMVI in rectal cancer, a metaanalysis including the data gathered in Chapter 3 was undertaken 721 . Briefly, a systematic search was performed of PubMed, Embase, MEDLINE, PubMed Central, and Cochrane electronic databases for articles pertaining to CIMP and rectal cancer.…”
Section: The Cpg Methylator Phenotype and Extramural Vascular Invasionsupporting
confidence: 88%